2012
DOI: 10.1016/s0924-9338(12)75178-7
|View full text |Cite
|
Sign up to set email alerts
|

P-1011 - Mental health of medical students in different levels of training

Abstract: Objectives:Medical education and training can directly contribute to the development of psychological distress in medical students. This can lead to catastrophic consequences such as impaired academic performance, impaired competency, medical errors and attrition from medical school. This study aimed to assess the prevalence of psychological morbidity among Iranian medical students.Methods:This was a cross-sectional study. Samples of medical students in different levels of training (basic science, clinical cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
79
6
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(106 citation statements)
references
References 22 publications
17
79
6
4
Order By: Relevance
“…It may also have deeper impact on students' mental health, such as developing anxiety and social problems overtime. This is consistent with the findings of Jafari et al; (15) but Sherina et al found no association between the years of study in medical school and mental health (7) neither Assadi et al found any significant difference between undergraduate students, interns and postgraduates. (18) Although mean GHQ scores were not significantly different in three groups of socioeconomic status, the participants with lowest economic position had higher scores.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…It may also have deeper impact on students' mental health, such as developing anxiety and social problems overtime. This is consistent with the findings of Jafari et al; (15) but Sherina et al found no association between the years of study in medical school and mental health (7) neither Assadi et al found any significant difference between undergraduate students, interns and postgraduates. (18) Although mean GHQ scores were not significantly different in three groups of socioeconomic status, the participants with lowest economic position had higher scores.…”
Section: Discussionsupporting
confidence: 90%
“…This is somehow close to the findings of Jafari et al, who reported near half of their participants had scored above the normal point in GHQ-12. (15) But this finding of our study is much higher than the prevalence of mental health problems in Dubai medical students found by Ahmadi et al (16) The prevalence of mental morbidity was also higher among our participants compared with Turkish and Nepalese medical students, which are 48% and 20.9% respectively. (21,22) We found higher percentage of abnormal mental health status among our participants in comparison to a study conducted in Tehran University of Medical Sciences, which was 43.9%.…”
Section: Discussioncontrasting
confidence: 79%
See 3 more Smart Citations